A Missing Piece of RSS Technology - Ladda PREECHAVEERAKUL; Wichuta KAEWNOPPARAT; Dararat SAELEE (Informatică economică, 2009)
In the Information Age, people use RSS (Really Simple Syndication) Technology to help them to easily get the latest contents from websites by accessing only a single website as well as by using mobile devices. Several companies have started to use RSS for distributing their information to customers. However, most contents published via RSS technology are public and not confidential such as credit card information, financial business information etc. Since the RSS technology does not have a mechanism to ensure that the incoming information is really secure, in this paper we have proposed a Secure Information Notifying System with RSS Technology (SInfoNS). We have applied the RSS technology together with the cryptography to make any RSS document become secure before disseminating it to relevant users. The SInfoNS also uses XSL to apply to private information retrieval and XML schema and SchemaPath definitions have been created for validation. The results displayed on a user's mobile device provide users with the latest information. The results of this study confirm that our system will aggregate RSS documents and disseminate information to each user. The SInfoNS enables RSS technology for the use of private information that can be securely distributed.